Terraforming and monumentality as long-term social practice in the Salish Sea region of the Northwest Coast of North America. Issue 1 (December 2017) - Grier, Colin; Angelbeck, Bill; McLay, Eric
Abstract : The archaeological record of hunter-gatherer-fishers in the southern Gulf Islands of the Northwest Coast provides evidence of large-scale construction of shell mounds and ridges, houses and villages, production features, defensive earthworks and burial mounds and cairns. Landscapes were terraformed – meaning anthropogenically constructed, modified and maintained – in service of multiple ends. These practices had significant implications for the construction of place, community, social inequalities and political dynamics over the long term. We document the scope of landscape construction and terraforming in the archaeological record of the Salish Sea, focusing on its spatial, temporal and social elements in the southern Gulf Islands. Monumental constructions were widespread in the area, in most cases emerging in an iterative manner over the past 5000 years. However, over the last 1500 years, more short-term and larger-scale episodes of construction are evident, potentially connected with increased sociopolitical inequalities and their contestation. Our overarching objective is to consider how monumentality and terraforming have shaped Coast Salish histories, and better establish how monumentality articulated with the reproduction of society.